International Cooperative Comparison of Instrument Methods for Cooked Rice Texture - Juliano, Bienvenido O.; Perez, Consuelo M.; BARBER, SALVADOR; Blakeney, Anthony B.; IWASAKI, TETSUY A.; SHIBUYA, NAOTO; KENEASTER, KENNETH K.; CHUNG, SOOMI; LAIGNELET, BERNARD; LAUNAY, B.; DEL MUNDO, ANGELITA M.; Suzuki, Hiroshi; et al. (Wiley, 1981)
The texture of 10 milled rices cooked by a standardized method in excess water was measured in 11 laboratories using various instrument methods that had been developed specifically for national samples. The samples selected represented a wide range of rice textures. Instrument indexes for hardness and stickiness of cooked rice generally were more sensitive than the corresponding taste panel scores in discriminating among the 10 cooked rice samples. Instrument indexes for hardness correlated positively among each other as did those for stickiness. Most hardness indexes showed significant negative correlation with stickiness indexes. Most hardness indexes were positively correlated with amylose content whereas stickiness indexes were negatively correlated with amylose content. The continued use of amylose content as an index of eating quality in a rice breeding program is justified.